Adsorption Cooling System Using Metal-Impregnated Zeolite-4A - Somsuk Trisupakitti; Jindaporn Jamradloedluk; Songchai Wiriyaumpaiwong (Advances in Materials Science and Engineering)
The adsorption cooling systems have been developed to replace vapor compression due to their benefits of being environmentally friendly and energy saving. We prepared zeolite-4A and experimental cooling performance test of zeolite-water adsorption system. The adsorption cooling test-rig includes adsorber, evaporator, and condenser which perform in vacuum atmosphere. The maximum and minimum water adsorption capacity of different zeolites and COP were used to assess the performance of the adsorption cooling system. We found that loading zeolite-4A with higher levels of silver and copper increased COP. The Cu6%/zeolite-4A had the highest COP at 0.56 while COP of zeolite-4A alone was 0.38. Calculating the acceleration rate of zeolite-4A when adding 6% of copper would accelerate the COP at 46%.